UC Irvine: 1st place winner of the 2008 hiTEC product development competition - Sirivianos, Michael (My University, 2026)
April 2008: UC Irvine - 1st place winner of the 2008 hiTEC product development competition at the Bren School of Computer Science, and 3rd place winner in the 2008 SYCR business plan competition at the Merage School of Business for adball.com; a web site for crowdsourcing advertising campaigns.
Keywords: Sciences